Gadolinium-coordinated elastic nanogels for in vivo tumor targeting and imaging - Lim, Chang-Keun; Singh, Ajay; Heo, Jeongyun; Kim, Daehong; Lee, Kyung Eun; Jeon, Hyesung; Koh, Joonseok; Kwon, Ick-Chan; Kim, Sehoon (ELSEVIER SCI LTD, 2013)
Coordination polymer gels have been recognized as promising hybrid nanoplatforms for imaging and therapeutic applications. Here we report functional metal-organic coordinated nanogels (GdNGs) for in vivo tumor imaging, whose non-crystalline and elastic nature allows for long blood circulation, as opposed to the rapid systemic clearance of common nanohybrids with rigid/crystalline frameworks. The deformable structure of GdNGs was constructed by random crosslinking of highly flexible poly-ethyleneimines (PEI) with gadolinium (Gd3+) coordination. The in vitro characterization revealed that GdNGs have elasticity with an apparent Young's modulus of 3.0 MPa as well as minimal cytotoxicity owing to the tight chelation of Gd3+ ions. In contrast to common T-1-enhancing gadolinium complexes, GdNGs showed the capability of enhancing negative T-2 contrast (r(2) = 82.6 mm(-1) s(-1)) due to the Gd3+- concentrated nanostructure. Systemic administration of fluorescently labeled GdNGs with core and overall hydrodynamic sizes of similar to 65 and similar to 160 nm manifested efficient targeting and dual-modality (magnetic resonance/fluorescence) imaging of tumor in a mouse model. The minimal filtration by the reticuloendothelial system (RES) suggests that the structural deformability helps the large colloids circulate in the blood stream for tumor accumulation. The unusual performance of a large Gd3+-complexed colloid (minimal RES sequestration and high T-2 contrast enhancement) represents the versatile nature of nanoscopic organic-inorganic hybridization for biomedical applications. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: METAL-ORGANIC FRAMEWORKS; DRUG-DELIVERY; NANOPARTICLES; COMPLEX